2022
DOI: 10.1002/ps.7231
|View full text |Cite
|
Sign up to set email alerts
|

Residual efficacy of the neonicotinoid insecticide clothianidin against pyrethroid‐resistant Aedes aegypti

Abstract: BACKGROUND Here we report the residual efficacy of the neonicotinoid insecticide clothianidin against pyrethroid‐resistant Aedes aegypti. We first conducted a range‐finding evaluation of clothianidin on three different substrates (wall, wood, cloth) using three doses (100, 300 and 600 mg a.i. m−2) and conducting World Health Organization (WHO) cone bioassays to assess acute (24 h) and delayed (up to 7 days) mortality. In experimental houses located in Merida (Mexico) and using free‐flying pyrethroid‐resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…aegypti from the trial site showed that cone bioassays provide poor results in surfaces treated with SumiShield 50 WG compared to the insecticide's impact on free-flying mosquitoes (released in experimental houses). While delayed mortality in cones reached a maximum of 60% at 1 month post-spraying, delayed mortalities higher than 80% were maintained up to 7 months when mosquitoes were exposed in experimental houses 49 . This difference may be the product of the insecticide mode of action.…”
Section: Discussionmentioning
confidence: 94%
“…aegypti from the trial site showed that cone bioassays provide poor results in surfaces treated with SumiShield 50 WG compared to the insecticide's impact on free-flying mosquitoes (released in experimental houses). While delayed mortality in cones reached a maximum of 60% at 1 month post-spraying, delayed mortalities higher than 80% were maintained up to 7 months when mosquitoes were exposed in experimental houses 49 . This difference may be the product of the insecticide mode of action.…”
Section: Discussionmentioning
confidence: 94%